Pengembangan Modul Fisika Berbasis QR-CODE pada Pokok Bahasan Fisika Inti Kelas XII SMA - Sari Badriana; Heny Apriani; Mega Marito (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2021)
The development of this module is based on the learning process that has used internet media, but in fact its use during the learning process has not been maximized and the use of the internet for learning has not been able to direct students to achieve learning goals. The purpose of this research is to produce a product in the form of a QR Code-based module with core physics as a learning resource for class XII physics that is suitable for use by students. This development research uses the ADDIE model which only takes 4 stages, namely Analysis (Analysis), Design (Design), Development (Development), Implementation (Implementation). Based on the results of the analysis, the percentage of validity results obtained from media experts 75%, material experts 78.125%, linguists 74.5%, and trials to groups of students with 91.66% results. Based on the results of the validation that has been carried out, the QR Code-based physics module with the core physics subject of class XII is feasible and effective to be used as a physics learning medium.